An introductory of a content provider agent in higher learning institutions - Sugathapala, B. A. Jessica Malani; Md Sultan, Abu Bakar (2011)
Software agents, nowadays has become most favorable technology in developing computer systems. Software agent can be used to quickly and easily build integrated agent-based systems where agents can be applied in all domains of interest and one of them is in education. In the higher learning institution, lecturers are optimize with workloads such as lecturing, lecture preparation, student consultation and lecture content/module preparation etc. Looking at the current ways of materials preparation done by lecturers, the process might take hours, days and even months in order to prepare impressive teaching materials for students. In order to minimize the workload, therefore the author had proposed and developed a content provider agent (CPA) in order to assist lecturer in preparing teaching contents as requested. Evaluation is done by comparing the percentage of effective search process done by the CPA and the search done via search engines. The result is promising where the proposed agent satisfy the objectives of the CPA developed.